2023
DOI: 10.3389/fpls.2023.1243323
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evolution of bZIP transcription factors in Malvales and functional exploration of AsbZIP14 and AsbZIP41 in Aquilaria sinensis

Hao Zhang,
Xupo Ding,
Hao Wang
et al.

Abstract: IntroductionAgarwood, the dark-brown resin produced by Aquilaria trees, has been widely used as incense, spice, perfume or traditional medicine and 2-(2-phenethyl) chromones (PECs) are the key markers responsible for agarwood formation. But the biosynthesis and regulatory mechanism of PECs were still not illuminated. The transcription factor of basic leucine zipper (bZIP) presented the pivotal regulatory roles in various secondary metabolites biosynthesis in plants, which might also contribute to regulate PECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 108 publications
1
7
0
Order By: Relevance
“…These are later than the origin time of A. sinensis , which is around 108.89 Mya ( Figure 2 b). These divergence times of the species are similar to those in previous reports [ 11 , 16 , 17 ]. As the outgroups, Amborella trichopoda and Vitis vinifera did not contain the Bi gene in their genomes.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These are later than the origin time of A. sinensis , which is around 108.89 Mya ( Figure 2 b). These divergence times of the species are similar to those in previous reports [ 11 , 16 , 17 ]. As the outgroups, Amborella trichopoda and Vitis vinifera did not contain the Bi gene in their genomes.…”
Section: Resultssupporting
confidence: 91%
“…The functional gene transformation was performed on tobacco ( Nicotiana benthamiana ) plants that were grown in a growth chamber for 40 days. The plants were grown in pots filled with a soil and vermiculite mixture (2:1) under a photoperiod cycle of 16 h lightness and 8 h darkness at 25 °C and 70% relative humidity [ 17 ]. The seeds of N. benthamiana were obtained from the laboratory of Dr. Yuan Yao in our institute.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, subcellular localization of DlbZIP60 containing a GFP tag was performed on onion after infestation, and the results showed that it was localised to the nucleus. Previous studies have found that Toothbrush ( Aquilaria sinensis ) AsbZIP14-GFP or AsbZIP41-GFP [ 43 ], Bletilla ( Bletilla striata ) BsbZIP13-GFP [ 44 ], Tomato ( Solanum lycopersicum L.) SlbZIP06 -GFP, SlbZIP12-GFP, SlbZIP16-GFP, SlbZIP32-GFP and SlbZIP46-GFP [ 8 ] were all located in the nucleus. This observation indicated that DlbZIP60, which may use the nucleus as the beginning of transcription, involves in multiple hormonal regulatory pathways in D. longan and affecting SE.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion and contraction of NAC families were examined by reconstructing two phylogenetic trees: a phylogenetic tree of 12 plant species with 302 single-copy genes [41] and an evolutionary tree of all 1502 NAC genes. The results showed that a total of 84 ancestral genes were duplicated in the lineages that led to the common ancestor of A. trichopoda, A. thaliana, V. vinifera and Malvales plants.…”
Section: Comparative Evolutionary Analysis Of the Nac Family In Malvalesmentioning
confidence: 99%
“…Our recent studies have demonstrated that the transcription factors in A. sinensis were also involved in the regulation of AsPKS expression, such as AsMYB054, which was the repressor in the transcripts of AsPKS02 and AsPKS09 [39]. It is interesting that a syntenic gene pair of AsbZIP14 and AsbZIP41 presents a different interaction with AsPKS from the same subtype of typical type III PKS, especially for AsbZIP14, which activated the expression of AsPKS08 and repressed the expression of AsPKS09 [41]. By combining bioinformatics analysis and gene expression data, we also identified two candidate genes that may be associated with the accumulation of PECs (Figure 8).…”
Section: Possible Role Of Nac Genes In Secondary Metabolite Synthesis...mentioning
confidence: 99%